(untitled) (International Journal of Physiotherapy, 2017)
Background: Traumatic brain injury (TBI) is one of the main reasons of death and disabilities globally, mainly in kids and adolescence and is still being considered as an enduring issue in ICUs. There are no definite rehabilitation methods for traumatic brain injury patients. The frequent techniques administered by physiotherapists in ICU are positioning, mobilization, manual hyperinflation technique (MHT), percussion, vibrations, suction, cough, and breathing exercises. Case Summary: This study was done in the Medical ICU at Liaquat National Hospital and Medical College, Karachi, Pakistan. The chief complaints of the patient was gunshot injury to the right temporal region. The patient was diagnosed with right front parietal contusion with a fracture of the right temporal bone, subarachnoid edema, and midline shift. The physiotherapy interventions given to the patient were Chest Physical Therapy (CPT) with Zero-pressure Manual Hyperinflation and percussions. Once the ICP issues were controlled, manual hyperinflation with 30 cm of H2O, modified postural drainage, minimal–handling saline suctioning were applied. After extubation, CPT included Active Cycle of Breathing Techniques (ACBTs), volume oriented incentive spirometry, motor relearning program, and mobilization. The outcome measures were secretion status, modified rancho los amigos level of cognitive functioning scale, and arterial blood gas analysis. Results: The patient’s secretions status improved from P1 to M1, FiO2 was improved from 40% to 21%, chest wall volume was increased from 200 cc/sec to 600 cc/sec, and RLA level increased from I to VIII. Conclusion: The case study presents that physiotherapy interventions used in intensive care units may prevent pulmonary complications in sufferers with traumatic brain injuries. It also suggests that early mobilization should be done to improve cognitive functioning and behavior. This study may also indicate that the earlier the patient is started with mobilizations and rehabilitation, the less costly it will be for the patient.